Papan Edukasi Penguraian Sampah Sebagai Inisiatif Lingkungan Di Kelurahan Kubang Sirakuk Selatan Kota Sawalunto - Lili Dasa Putri; Nasywaa Aliyyah Jonnnedi; Fadiyah Septia Melza; May Christina Halawa; Alysa Putri Mulianda; Widya Hernalis (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2026)
The issue of waste remains a serious challenge in Indonesia, particularly due to a lack of public awareness regarding the long-term impact of inorganic waste. The Community Service Program (KKN) of students from the University of Padang in Kubang Sirakuk Selatan Village, Sawalunto City, addressed this issue by designing and implementing the “Waste Decomposition Educational Board” program. The primary objective of this initiative was to raise public awareness through visual media that convey information about types of waste and their estimated decomposition times in nature. The implementation methods included site surveys, content design, the creation of educational boards using recycled materials, and their installation at strategic locations near schools and main roads. An evaluation was conducted 20 days after installation through direct interviews with residents, showing that the presence of the information boards effectively improved residents' understanding and behavior in managing waste. This activity also supports the achievement of SDGs points 11 and 12, particularly in creating sustainable communities and responsible consumption and production. The results of this program show that visual media-based environmental education in public spaces can be an effective tool for transforming community behavior toward waste issues.